2013
DOI: 10.1080/00981389.2012.742482
|View full text |Cite
|
Sign up to set email alerts
|

Coping Skills Among African-American Breast Cancer Survivors

Abstract: Women with a diagnosis of breast cancer, particularly African-American women, face multiple barriers to survival. Although research exists regarding the unique barriers faced by African-American breast cancer survivors, there has been little research into the various coping needs or coping strategies used among African-American women. The purpose of this article is to provide information from an exploratory study of data investigating the coping skills of 30 African-American women diagnosed and treated for bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Cancer has become one of the leading causes of death in China [ 3 ]. Patients with cancer often experience more feelings of shock, fear, uncertainty, and loss of control than those with many other diagnoses [ 4 ], and appropriate informational support is vital in helping cancer patients cope with negative feelings and conditions [ 5 , 6 ]. Other positive effects of adequate and appropriate informational support have also been identified in several studies, including increased involvement in the decision-making process [ 7 ], increased satisfaction with treatment choices [ 8 ], and better quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer has become one of the leading causes of death in China [ 3 ]. Patients with cancer often experience more feelings of shock, fear, uncertainty, and loss of control than those with many other diagnoses [ 4 ], and appropriate informational support is vital in helping cancer patients cope with negative feelings and conditions [ 5 , 6 ]. Other positive effects of adequate and appropriate informational support have also been identified in several studies, including increased involvement in the decision-making process [ 7 ], increased satisfaction with treatment choices [ 8 ], and better quality of life [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression symptoms may result from an inability to successfully cope with a cancer diagnosis and treatment [28]. The relevance for coping support across cancer survivorship is explained, in part, by the stress and coping theory [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies among nonethnic minority women have identified several coping strategies relevant across the cancer survivorship continuum, including faith, fatalism, optimism, fighting spirit, information seeking, denial, and avoidance (Towsley et al, 2007). It is noteworthy that an inability to successfully cope with cancer may lead to significant psychosocial distress (C. Davis, Rust, & Darby, 2013), which may affect a cancer survivor's ability to manage their posttreatment care and thus decrease quality of life in the aftermath of the diagnosis (Vachon, 2006). In this regard, the literature has indicated that approximately one third of BCS experience significant distress and/or impairment of functioning in their lives (Coyne, Palmer, Shapiro, Thompson, & DeMichele, 2004;Hegel et al, 2006).…”
mentioning
confidence: 99%